Question

\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Find: } f \circ g(x) \]

Ask by Pearson Greene. in Nigeria
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( f \circ g(x) = 6x - 5 \)

Solution

Simplify the expression by following steps: - step0: Add the terms: \(3\left(2x-3\right)+4\) - step1: Expand the expression: \(6x-9+4\) - step2: Add the numbers: \(6x-5\) To find \( f \circ g(x) \), we need to substitute \( g(x) \) into \( f(x) \). 1. We have the functions: - \( f(x) = 3x + 4 \) - \( g(x) = 2x - 3 \) 2. Now, we substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(2x - 3) \] 3. Next, we calculate \( f(2x - 3) \): \[ f(2x - 3) = 3(2x - 3) + 4 \] 4. Expanding this expression: \[ = 6x - 9 + 4 \] \[ = 6x - 5 \] Thus, the result is: \[ f \circ g(x) = 6x - 5 \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To find \( f \circ g(x) \), which means \( f(g(x)) \), we'll first substitute \( g(x) \) into \( f(x) \). Given: \[ g(x) = 2x - 3 \] Now substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(2x - 3) = 3(2x - 3) + 4 \] Now simplify: \[ = 6x - 9 + 4 \] Combine like terms: \[ = 6x - 5 \] Thus, the final result is: \[ f \circ g(x) = 6x - 5 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy